Evaluation of Anthropometric and Metabolic Parameters in Obstructive Sleep Apnea - Yaşar Yildirim; Süreyya Yilmaz; Mehmet Güven; Faruk Kılınç; Ali Veysel Kara; Zülfükar Yilmaz; Gökhan Kırbaş; Alpaslan Kemal Tuzcu; Fatma Yılmaz Aydın (Pulmonary Medicine)
Aims. Sleep disorders have recently become a significant public health problem worldwide and have deleterious health consequences. Obstructive sleep apnea (OSA) is the most common type of sleep-related breathing disorders. We aimed to evaluate anthropometric measurements, glucose metabolism, and cortisol levels in patients with obstructive sleep apnea (OSA). Materials and Methods. A total of 50 patients with a body mass index ≥30 and major OSA symptoms were included in this study. Anthropometric measurements of the patients were recorded and blood samples were drawn for laboratory analysis. A 24-hour urine sample was also collected from each subject for measurement of 24-hour cortisol excretion. Patients were divided equally into 2 groups according to polysomnography results: control group with an apnea-hypopnea index (AHI) <5 (n=25) and OSA group with an AHI ≥5 (n=25). Results. Neck and waist circumference, fasting plasma glucose, HbA1c, late-night serum cortisol, morning serum cortisol after 1 mg dexamethasone suppression test, and 24-hour urinary cortisol levels were significantly higher in OSA patients compared to control subjects. Newly diagnosed DM was more frequent in patients with OSA than control subjects (32% versus 8%, p=0.034). There was a significant positive correlation between AHI and neck circumference, glucose, and late-night serum cortisol. Conclusions. Our study indicates that increased waist and neck circumferences constitute a risk for OSA regardless of obesity status. In addition, OSA has adverse effects on endocrine function and glucose metabolism.